Improving the provision of clinical pharmacy services in low- and middle-income countries: a qualitative study in tertiary health facilities in Tanzania - Fredrick Kalokola; Dorkasi L Mwakawanga; Ritah F Mutagonda; Hamu J Mlyuka; Wigilya P Mikomangwa; Manase Kilonzi; Wema A Kibanga; Alphonce Ignace Marealle; Bertha Mallya; Deogratias Katabalo; Sofia Sanga; John Rwegasha; et al. (BMJ Public Health)
Background The provision of clinical pharmacy services (CPS) in low- and middle-income countries is still low. The reported challenges in providing CPS include healthcare structures, public policies, resources, workforce, culture and education inequalities. This study aimed to explore the strategies to improve the provision of CPS in tertiary health facilities in Tanzania.Methods This study was conducted between August and September 2021. We adopted an exploratory qualitative study to conduct 14 in-depth interviews with hospital administrators and 10 focus group discussions (FGDs) with healthcare providers. A purposeful sampling technique was used to recruit 97 participants, including 45 pharmacists, 31 medical doctors and 21 nurses across five tertiary healthcare institutions. Of those, 14 hospital administrators participated in 14 IDIs and 83 healthcare workers divided into 10 FGDs. Analysis was done using a qualitative thematic approach.Results The study identified several strategies that fall under four major themes: (i) strengthen preservice training by reviewing the Bachelor of Pharmacy training curriculum to include clinical pharmacy components; (ii) improve continuing professional training through regular provision of on-job training to pharmacists; (iii) revise the scope of work for pharmacists to include CPS provision in the job description; and (iv) improve operational environment by ensuring availability of guidelines, policies, and adequate number of pharmacists and good inter-professional communication skills.Conclusions This study’s findings highlight that improving CPS provision requires strengthening pharmacists’ training, scope of work and operational environment. The latter calls for multifaceted engagement from pharmacists, training institutions, policymakers, regulatory bodies and health systems for sustainable progress.